A Note on sawing characteristics of rubber wood - Damodaran K (In: Abstracts of Papers: First National Seminar on Rubber Wood, 12 December 1989, Rubber Research Institute of India, Kottayam, Kerala, India, pp.. 33., 1989)
Rubber wood has emerged as most potential wood raw material in recent years in the country, particularly in Kerala State. Major use of rubber wood is in the form of sawn timber. The basic problem associated with the utilisation of rubber wood therefore, lies in evolving cost effective processing technology that could be easily adopted under the prevalent techno-economic conditions so as to achieve maximum recovery of quality product-sawn timber at a workable moisture content without any biological and physical degradation. Further processing of sawn rubber wood into value added end products like furniture, joinery, toys, etc., is rather competetive due to its inherent desirable properties medium density with low shrinkage and good stability, light attractive colour, uniform texture, good workability, fairly good strength properties and capability of receiving varieties of finishes. Effective utilisation of rubber wood largely depends on the developement of (1) suitable sawing practices for higher recovery at resonable productivity, (ii) grade sawing techniques and grading of sawn timber for different end uses, (iii) appropriate protective measures at every stage of processing which will ensure adequate service life for the end products and economic seasoning methods which minimise degradation. Research and development work towards achieving some of these objectives are in progress at the Indian Pluwood Industries Research Institute, Bangalore. The details of work being carried out and some of the finding so far made are discussed in this paper.
Keywords: Rubberwood